In Vitro Expression of Filarial SXPI Gene for the Development of a Nucleic Acid Based Vaccine - Abd. Majid, Roslaini (2005)
The objectives of this study were to clone gene that encode filarial SXPI protein followed by in vitm expression of the protein. The Special Programme for Research and Training in Tropical Diseases (TDR) WHO has advocated SXPl as one of the vaccine candidate to curb filarial infection. SXPl antigen has been reported to confer protective immunity, causing reduction of microfilaraemia levels in jirds (Meriones unguiculatus) blocking subsequent Brugia malayi infection. In this study, the gene that encode SXPl antigen was 517 bp in length and was extracted and amplified from the infective stage (L3) of subperiodic Brugia malayi. The gene was successfully cloned into replication vector p ~ ~ ~ 2(Inv. it1rog en) followed by subcloning into mammalian expression vector pVAXl (Invitrogen). The presence of SXPl gene in - both vectors were validated by polymerase chain reaction (PCR), restriction enzymes analysis (RE) and finally by automated sequencing. The cloned SXPl in pVAX was designated as pVAXISXP1. The plasmid bearing SXPI gene was transfected into two types of animal cell lines (COS-7 and CHO) using Polyfect Transfection Reagent (Qiagen). The successful expression of targeted gene in the mammalian cell lines were determined by RT-PCR and Western Blotting. The PCR product of the transfected cells was 517 bp on the agarose gel. In addition, the -20 kDa of expressed SXPl protein was detected on nitrocellulose membrane by rabbit polyclonal antibody against the SXPI protein. This study has successfully established the ground work for future deliberations towards the development of antibrugia transmission blocking genetic vaccine.